-59=-4n-3

Simple and best practice solution for -59=-4n-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -59=-4n-3 equation:


Simplifying
-59 = -4n + -3

Reorder the terms:
-59 = -3 + -4n

Solving
-59 = -3 + -4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '4n' to each side of the equation.
-59 + 4n = -3 + -4n + 4n

Combine like terms: -4n + 4n = 0
-59 + 4n = -3 + 0
-59 + 4n = -3

Add '59' to each side of the equation.
-59 + 59 + 4n = -3 + 59

Combine like terms: -59 + 59 = 0
0 + 4n = -3 + 59
4n = -3 + 59

Combine like terms: -3 + 59 = 56
4n = 56

Divide each side by '4'.
n = 14

Simplifying
n = 14

See similar equations:

| 8-3x+2x=3(x+4) | | 25-7v=10(v-6) | | F(x)=105x | | 10y+5x=30 | | 2c+10=c-2 | | -12x=-228 | | 12x+32=10+y | | 2y^2-6x+1=0 | | 3m^3+192= | | -70=14n | | 12(600)=x | | 2(-3x+5)-6x=-3(x+4) | | 14-5x+9x=-2(-7x+3) | | 8n-17=0 | | x^2-2xy+8=0 | | x-9=3x+15 | | -9x+1=2x-8 | | 3(y-6)=8y+22 | | P-3=11 | | 7+4=27 | | 6x+9=-4 | | N-3=-21 | | 2cosx=2-3sinx | | N-3=-23 | | -5w+3(w+5)=27 | | N^2+3n-128=0 | | K+12=1 | | 30-10x=-7(6-x) | | 7h+9=32 | | 19=a+1 | | 6p-6+40p=2+34p | | 6x+5-8x=-(2x-5) |

Equations solver categories